PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK DALAM MENCIPTAKAN LOYALITAS NASABAH TABUNGAN SERTA DAMPAKNYA TERHADAP KEPUASAN NASABAH BANK DANAMON CABANG PEKANBARU - Dea Lakcinta Rani; Alvi Furwanti Alwie; Andewi Rakhmawati (Jurnal Economica, 2019)
Customer Loyalty has been a bank need to raise third party fund that has low rate of fund by increase the customer satisfaction. This research found there was a theory gap that Danamon achievement in nationally good service quality award can’t increase the third party fund in 2014-2015. This Research is quantitative research using the Path Analysis by Partial Least Square approach. The data collection using questionnaire for 133 sample of 893 population that is Customer of Danamon Bank in Pekanbaru Branch. The Result of this research show that service quality, produk quality and customer satisfaction has positive and significant effect to Customer Loyalty, so that the finding of the research that there is lack of product quality and service quality locally need to be optimalized by using both technology and service adjustment